PENGGUNAAN PBL DENGAN TUTOR SEBAYA DAN Hp DALAM UPAYA MENINGKATKAN PEMBELAJARAN POLINOMIAL - Retno Antik Gianti (Jurnal Ilmiah Pendidikan TRISALA, 2021)
At first the teacher saw the participants' low mathematics learning outcomes. Of the several problems, students' understanding problems in mathematics learning, teacher learning are still conventional, and most students are less active in participating in mathematics learning.The teacher uses the Problem Based Learning (PBL) model with peer tutors utilizing Information and Communication Technology facilities, namely Mobile (Hp). PBL emphasizes more on motivating students, in problem solving activities that can explain and solve problems given by the teacher, in addition to learning from the teacher, students get learning from their friends, so they become active. From seeing the activeness of students in the initial condition, they were less active to being active in cycle 1 and cycle 2. Learning activeness increased to be active by 51% in cycle 1, and to 63% in cycle 2. The increase in student learning achievement can be seen from the average Classical mean of learning outcomes from the initial conditions 46.1 to the final conditions 70.5. The completeness of learning the initial conditions of the 33 students was low, namely 6%, increased in cycle 1 was obtained 33.3% and increased to 63.6% in cycle 2. The results achieved from the Polynomial mathematics learning activities of class XI IPA SMA Negeri 3 Salatiga by using PBL with Peer Tutors and Hp shows that it can increase the activeness, process skills, and learning achievement of students.